Relationship between pregestational nutritional status and type of processing of foods consumed by high-risk pregnant women - Débora Cardoso Fernandes; Ioná Carreno; André Anjos da Silva; Tais Battisti Guerra; Fernanda Scherer Adami
Abstract Objectives: to relate pregestational nutritional status, maternal age and number of pregnancies to the distribution of macronutrients and micronutrients according to the type of processing offoods consumed by high-risk pregnant women. Methods: a retrospective cross-sectional study was carried out with data from medical records of 200 pregnant women served by a public outpatient clinic in Rio Grande do Sul from 2014 to 2016. Results: the mean percentages of lipids, monounsaturated fatty acids, polyunsaturated fatty acids and sodium intake were higher among ultra-processed foods. There was a significant inverse correlation between maternal age and total calorie intake (p=0.003) and percentage of carbohydrates (p=0.005) and proteins (p=0.037) from ultra-processed foods. There was also a significant association between pregestational nutritional status and total calorie intake (p=0.018) and percentage of carbohydrates (p=0.048) from ultra-processed foods. Conclusions: the mean percentages of lipids, monounsaturated fatty acids, polyunsaturated fatty acids and sodium intake were higher among ultra-processed foods. It was observed that the older the maternal age of high-risk pregnant women, the lower the intake of total calories and percentages of carbohydrates and proteins from ultra-processed foods. It was also observed that pregestational nutritional status was significantly associated with the intake of total calories and percentage of carbohydrates from ultra-processed foods.